Reliability of time to exhaustion analyzed with critical-power and log-log modeling - Hinckson, E. A.; Hopkins, W. G. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The large variability of time to exhaustion between repeated tests at constant power output or speed gives an impression that these tests are unsuitable for monitoring athletic performance. We have addressed this issue using critical-power and log-log models of the speed-duration relationship to analyze treadmill runs.